2013
DOI: 10.1039/c3cc44072a
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of mammalian cells with stimuli-responsive polymers

Abstract: In order to introduce alternative functions into mammalian cells and control them under ambient conditions, poly(N-isopropyl acrylamide) (PNIPAM) was immobilized on the cell surface. Cellular aggregation could be regulated by temperature change. In addition, separation of PNIPAM-conjugated glycoproteins was successfully performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
(15 reference statements)
0
16
0
Order By: Relevance
“…Biocompatibility issues have motivated the development of stimuli-responsive polymers of diverse chemical structures, in order to optimize responses in serum (Francis MF et al 2001) for cell agglomeration (Iwasaki Y et al 2013) permeabilization of mammalian cells, or biocide activity (see Figure 2 for illustrations on T-responsive and light-responsive polymers, or for pH-triggered ones: (Henry SM et al 2006), (Lackey CA et al 1999), (Eccleston ME et al 2000), (Kusonwiriyawong C et al 2003)). The exact origin of stimuli-controlled membrane disruption is to date largely conjectural.…”
Section: Iic Controlling the Degree Of Polymer Insertion In Membranmentioning
confidence: 99%
See 1 more Smart Citation
“…Biocompatibility issues have motivated the development of stimuli-responsive polymers of diverse chemical structures, in order to optimize responses in serum (Francis MF et al 2001) for cell agglomeration (Iwasaki Y et al 2013) permeabilization of mammalian cells, or biocide activity (see Figure 2 for illustrations on T-responsive and light-responsive polymers, or for pH-triggered ones: (Henry SM et al 2006), (Lackey CA et al 1999), (Eccleston ME et al 2000), (Kusonwiriyawong C et al 2003)). The exact origin of stimuli-controlled membrane disruption is to date largely conjectural.…”
Section: Iic Controlling the Degree Of Polymer Insertion In Membranmentioning
confidence: 99%
“…Antimicrobial agents with selectivity modulated by side groups, (Kuroda K et al 2009;Palermo EF et al 2009a;Palermo EF et al 2011;Palermo EF et al 2009b) Pegylated poly(lysine) (or not shown poly(ethylene imine)) for mild cell adhesion, and LbL coating. (Mansouri S et al 2011), (Wilson JT et al (Ho VHB et al 2011)) or pH-responsive endosomal escape in mammalian cells (poly(acrylic acid) derivatives from (Henry SM et al 2006), (Yessine MA et al 2004)), or poly(lysylphtalate) derivatives with pH-sensitive hemolytic activity (Chen R et al 2009) Temperature-triggered biocide, (Iwasaki Y et al 2013;Mattheis C et al 2013;Mattheis C et al 2012) Light-triggered cytosolic penetration of additives in mammalian cells (Sebai S et al 2010), temperature-triggered biocide activity, samples from 2 to 7 correspond to increasing fraction (from 10 mol% to 54 mol%) of the amino-monomer in the copolymer also shown in Table 1 with transition temperature being in the range 32°C-36°C; (Mattheis C et al 2012) (B) lighttriggered penetration of peptides in cell. Other possible stimuli include temperature or pH.…”
Section: Neutral Chainsmentioning
confidence: 99%
“…[ 8 ] PNIPAM-functionalized nanostructures possess temperature switched bioadhesive properties. [ 9 ] There are very few reports on the application of schizophrenic micelles even though lots of works have been reported to study the physiological properties of such micelles. [ 3,10 ] In this paper, we systematically study the schizophrenic behavior of PAA-b -PNIPAM diblock copolymer.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its thermoresponsive property, PNIPAM has been investigated to fabricate thermoresponsive micelles or hybrid nanostructures for controlled drug release . PNIPAM‐functionalized nanostructures possess temperature switched bio‐adhesive properties …”
Section: Introductionmentioning
confidence: 99%
“…the biomaterial, is minute and hence the possible cytotoxic or immune responses are minimised. Current cell aggregation methods via CSR include direct cell membrane biotinylation, [16][17][18][19] covalent crosslinking, 20,21 and polyelectrolyte [22][23][24] or ionic mediated cell aggregation. [25][26][27] The further development of such biomaterial-cellular ensembles at the nanoscale is of paramount importance in order to mimic the mechanical, biochemical and interaction cues that occur in the physiological setting.…”
mentioning
confidence: 99%